THE RELATIONSHIP BETWEEN WORK DISCIPLINE, ORGANIZATIONAL COMMITMENT, AND JOB SATISFACTION TOWARD ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AMONG VOCATIONAL HIGH SCHOOL EDUCATORS IMPLEMENTING THE REGULAR GOVERNMENT-FUNDED TEACHING FACTORY PROGRAM IN JOMBANG REGENCY - Sholichatun Aisah Rahmawati; Saiful Anwar; Ichwani Siti Utami (Yayasan Education and Social Center, 2026)
This study aims to analyze the relationship between work discipline, organizational commitment, and job satisfaction toward Organizational Citizenship Behavior (OCB) among teachers of Vocational High Schools (SMK) implementing the Government Assistance Teaching Factory (TeFa) Regular Program in Jombang Regency. OCB refers to voluntary work behavior that exceeds formal job responsibilities and contributes to organizational effectiveness. In the context of vocational education, particularly in the implementation of Teaching Factory programs, OCB plays a crucial role because teachers are required not only to perform instructional duties but also to support an industry-based work culture through cooperation, loyalty, and active participation in school activities. This study employed a quantitative approach using a survey method. The research population consisted of teachers at SMKs implementing the Teaching Factory program in Jombang Regency. Data were collected through questionnaires measuring the variables of work discipline, organizational commitment, job satisfaction, and OCB. The data were analyzed using correlation and regression analysis to determine the relationships and effects among variables. Preliminary findings indicated that teachers demonstrated a high tendency of OCB, as reflected in the dimensions of altruism, conscientiousness, sportsmanship, courtesy, and civic virtue. The findings of this study are expected to show that work discipline, organizational commitment, and job satisfaction have positive and significant relationships with OCB, both partially and simultaneously. This study provides empirical contributions to the development of human resource management in vocational high schools, particularly in strengthening a positive work culture to support the success of vocational education revitalization programs through the Teaching Factory approach.